DETERMINASI KETEPATAN WAKTU PELAPORAN KEUANGAN: DETERMINATION OF THE TIMELINESS OF FINANCIAL REPORTING - Zirman Zirman; Supriono Supriono; Duhan Nadra (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2023)
The aim of this research is to examine and assess the connection between timely financial reporting and profitability, size of company, leverage, audit opinion, and outsider ownership. Companies in the mining sector that were traded on the Indonesia Stock Exchange between 2017-2019 make up the study's sample. 42 data from three years of observation were included in the research sample, which was selected intentionally. Utilizing logistic models, regression analysis is performed. The results of the research indicate that the timing of financial reporting is affected by profitability, business size, and audit opinions. However, leverage has no effect on how quickly financial reports are made.